Post‐'Brexit' Financial Governance: Which Dispute Settlement Framework Should Be Utilised?. Issue 1 (7th October 2019) - Howell, Elizabeth
Abstract: This contribution to the ongoing Brexit discussions addresses topical legal and regulatory issues in the post‐Brexit policy debate, especially the questions surrounding the important area of financial governance and dispute resolution. Specifically, a number of future UK/EU legal disputes with respect to financial services may emerge post‐Brexit. The article examines the UK's track record at the Court of Justice of the European Union, and discusses some likely future challenges. It then considers which institutional framework should be used for resolving disagreements. The article assesses the strengths and weaknesses of three potential models (the proposed Swiss/EU institutional framework; the EFTA 'docking' option; and the WTO system) and provides an original cross‐model evaluation. It also discusses the associated design challenges that EU and UK negotiators may encounter in the attempt to devise a post‐Brexit dispute settlement system.